Letter from the Editor: Why Are Papers Desk Rejected at European Accounting Review?. Issue 3 (3rd July 2017) - Stolowy, Hervé
Abstract: The aim of this note is to present desk rejections made by EAR in 2016 and also to provide some suggestions to authors in order to avoid these desk rejections.